AKTIVITAS ANTIBAKTERI EKSTRAK FERMENTAT ISOLAT FUNGI ENDOFIT KODE IFAZ-6 DARI AKAR BIDARA (Ziziphus mauritiana Lam.) TERHADAP BAKTERI Streptococcus mutans - Fitriana, Fitriana; Amirah, Sitti; Rahman, Safriani; Charawati, Nurul Mega (As-Syifaa Jurnal Farmasi, 2025)
Endophytic fungi are microorganisms that reside within plant tissues and are known to produce secondary metabolites with antibacterial potential. This study aimed to evaluate the antibacterial activity of the fermented extract of the endophytic fungal isolate IFAZ-6, derived from the roots of Ziziphus mauritiana Lam. (bidara), against Streptococcus mutans. The isolate was fermented for 21 days and extracted using ethyl acetate. The extract was tested for antibacterial activity using Minimum Inhibitory Concentration (MIC) at concentrations ranging from 0.2% to 25.6%, Minimum Bactericidal Concentration (MBC) from 3.2% to 25.6%, and agar diffusion assay at concentrations of 8%, 12%, and 16%. Inhibition zone diameters were analyzed statistically using the Kruskal–Wallis test followed by the Mann–Whitney post hoc test to assess differences between concentration groups. The results showed an MIC value of 3.2% and an MBC of 6.4%. The agar diffusion assay revealed a maximum inhibition zone diameter of 9.86 mm at 16% concentration, with statistically significant differences between concentrations (p < 0.05). These findings suggest that the fermented extract of IFAZ-6 possesses antibacterial activity against S. mutans, although its efficacy remains lower than that of the positive control, chloramphenicol